Remote ischaemic conditioning in necrotising enterocolitis: a phase I feasibility and safety study. Issue 1 (8th August 2022) - Zozaya, Carlos; Ganji, Niloofar; Li, Bo; Janssen Lok, Maarten; Lee, Carol; Koike, Yuhki; Gauda, Estelle; Offringa, Martin; Eaton, Simon; Shah, Prakeshkumar S; Pierro, Agostino
Abstract : Objective: Remote ischaemic conditioning (RIC) improves the outcome of experimental necrotising enterocolitis (NEC) by preserving intestinal microcirculation. The feasibility and safety of RIC in preterm infants with NEC are unknown. The study aimed to assess the feasibility and safety of RIC in preterm infants with suspected or confirmed NEC. Design: Phase I non-randomised pilot study conducted in three steps: step A to determine the safe duration of limb ischaemia (up to 4 min); step B to assess the safety of 4 repeated cycles of ischaemia-reperfusion at the maximum tolerated duration of ischaemia determined in step A; step C to assess the safety of applying 4 cycles of ischaemia-reperfusion on two consecutive days. Setting: Level III neonatal intensive care unit, The Hospital for Sick Children (Toronto, Canada). Patients: Fifteen preterm infants born between 22 and 33 weeks gestational age. Intervention: Four cycles of ischaemia (varying duration) applied to the limb via a manual sphygmomanometer, followed by reperfusion (4 min) and rest (5 min), repeated on two consecutive days. Outcomes: The primary outcomes were (1) feasibility defined as RIC being performed as planned in the protocol, and (2) safety defined as perfusion returning to baseline within 4 min after cuff deflation. Results: Four cycles/day of limb ischaemia (4 min) followed by reperfusion (4 min) and a 5 min gap, repeated on two consecutive days was feasible and safe in all neonates with suspected or confirmed NEC. Conclusions: This study is pivotal for designing a future randomised controlled trial to assess the efficacy of RIC in preterm infants with NEC. Trial registration number: NCT03860701 . Abstract : In a small phase 1 pilot study in preterm infants with suspected or confirmed necrotizing enterocolitis, cycles of remote ischemic conditioning with short duration of limb ischemia using a sphygmomanometer followed by reperfusion and rest was feasible and safe.